Evaluating the impact of introducing social norms statements on rape myth acceptance among Division III male athletes - Hirsch, Dan, author; McKelfresh, David, advisor; Barone, Ryan, advisor; Kilmer, Jason, committee member; Folkestad, James, committee member; Siller, Tom, committee member (Colorado State University. Libraries, 2019)
Sexual violence on college campuses is a serious and pervasive issue facing higher education in the United States. Social norms interventions provide a promising framework for reducing sexual violence on college campuses. Some research has been conducted using social norms interventions with student athletes, but the findings are inconsistent between Division I and III levels. The purpose of this study was to a) examine the role and impact of social norms and rape myth acceptance (RMA) among male student athletes at Division III programs and b) better understand the influence of normative clarification on male student athlete behavior in small school settings. A survey was distributed to over 200 male, student athletes at a small, private, liberal arts institution and was comprised of three instruments: 1) the Student Athlete Social Norms Survey, 2) the Hypermasculinity Inventory and 3) the Illinois Rape Myth Acceptance Scale. Participants were placed into three different test conditions (no norms / control, high norms and low norms) to measure the influence of normative statements on their rape myth acceptance. No statistically significant differences were found between levels of rape myth acceptance across the intervention groups. The findings support earlier studies that found differences in the impact of normative campaigns between Division I and Division III student-athletes.
Keywords: rape myth; Division III; student athlete